Attitudes Surrounding Music of Patients With Anorexia Nervosa: A Survey-Based Mixed-Methods Analysis - Krishna Priya, Aishwarya; Applewhite, Briana; Au, Katie; Oyeleye, Oyenike; Walton, Emma; Norton, Caroline; Patsalos, Olivia; Cardi, Valentina; Himmerich, Hubertus (Frontiers in Psychiatry, 2021)
Anorexia nervosa (AN) is one of the main eating disorders. It has the highest mortality of all psychiatric disorders, and the success rates of current therapies are not fully satisfactory. Thus, there is a need for novel interventions. We investigated the attitudes surrounding music of 41 patients with clinically-diagnosed AN as well as their thoughts on the potential therapeutic uses of music using a questionnaire of 50 questions. Free text responses were qualitatively analysed for reoccurring themes with NVivo 12 software. Yes/no questions and questions of best fit were analysed using the IBM SPSS Statistics version 25. The most prevalent theme was the positive effect of music. Most patients reported that listening to music evokes varying emotions in them (83%) which may be of positive or negative nature. Similarly, patients associated certain music with particular positive, but also with particular negative memories. A majority of patients stated that music helps to distract them (85%), helps with loneliness (59%) and helps them feel more connected to others (58%). This data indicates that people with AN make non-clinical use of music which seems to elicit positive as well as negative emotions and memories. Patients felt music is beneficial with regard to important aspects of AN, such as emotional problems, loneliness and relationship difficulties. Most of them would also like to attend music therapy.